Health Promotion in Israeli Colleges of Higher Education-The Example of Oranim College of Education - Irit Hof-Nahor; Seema Biswas (Frontiers Media S.A., 2020)
A teacher-training college that promotes a healthy learning environment contributes to the educational character of teachers of the future. These teachers adopt healthy lifestyles of their own and influence the lifestyles and learning of their pupils in kindergartens and schools. This article outlines the implementation of a health promotion program in a teacher-training college in northern Israel-Oranim College of Education. We describe the changes made at the college over three years-from the commitment of college executives to the health promotion policy initiative launched by the Ministry of Education, the appointment of a health leader (health promotion coordinator), staff and student engagement in change, rededication of college resources to healthy lifestyles and learning, promotion of healthy eating and exercise, changes in teaching, new courses and more interaction with the community, to health promotion by teachers in training in local kindergartens and schools. Using real examples, we show how effective policy implementation rests on the active participation of all stakeholders.